PENYELENGGARAAN PELAYANAN TERHADAP PEREMPUAN DAN ANAK KASUS KORBAN KEJAHATAN KEKERASAN DI POLRES KABUPATEN PADANG PARIAMAN - Yulia Nova; Tuti Khairani Harahap (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Services to women and children victims of violent crime cases are crucial issues that need attention. In an effort to protect victims of violent crime and to keep their rightness, Police of Padang Pariaman District provide RPK (Ruang Pelayanan Khusus) for women and children victims of violence crime, now it is known by the name of UPPA (Unit Pelayanan Perempuan Dan Anak). However, in practice there are still many problems of violence that can not be resolved properly. The same was found in the research by Tuti Khairani Harahap (2009) that in the implementation of policy dissemination through coordination with relevant agencies and the handling of cases accur in children, is still the presence of cases of cruelty, violence and persecution of women and children. As for the purpose of this study is to determine the implementation of services to women and children victims of crime cases in police station of Padang Pariaman district.The concept of theory is public service standards by Sianipar: the standard attitude of the personnel, service quality standards, standard of time, the standard of comfortable, safety standards and standard of costs and service of mechanism UPPA in PERKAP No.2, 2008. This study used qualitative research methods with an assessment of descriptive data. In collecting the data, researchers used interviewing techniques, observation and documentation. By using key informants as a source of information and as a source triangulation techniques in testing the validity of the data.The results of this study indicate that the implementation of services to women and children victims of crime in Police station of Padang Pariaman District to addressing violence against woman and children is not running optimally. because there are still many obstacles faced by officers and the victims themselves.Keywords: Implementation of Services, Violence Against Women and Children, Police Station of Padang Pariaman District